Exploring Non-English Major Students’ Perceptions Of Mobile Language Applications In Promoting Autonomous Learning - Allena Refi Rahmawati; Rahman Hakim; Zakaria Zakaria (Jurnal Intelek Insan Cendikia, 2025)
This research aimed to investigate non-English major students’ perceptions of mobile language applications in supporting their autonomous learning. 36 non-English major students from the Faculty of Economics and Business at Universitas Sultan Ageng Tirtayasa participated in this research. Quantitative and qualitative methods (mixed methods) were used to conduct the study. By implementing an explanatory sequential design with a Likert scale questionnaire and semi-structured interviews, the research data were collected. The quantitative data were analyzed using descriptive statistics, and the qualitative data were analyzed based on Miles and Huberman’s theory. The Data Analysis feature of Microsoft Excel was also employed to process the quantitative data. The results showed that the Duolingo application is the most frequently used mobile language application by non-English major students; 91.7% (33 non-English major students) chose this app. They also expressed positive perceptions of using mobile language applications to support their autonomous learning, despite several challenges and technological limitations, such as poor internet connections, lack of interaction, and restrictions in the free features. Moreover, non-English major students reported in the interviews that mobile language applications often provide only brief explanations or feedback, and the lack of interaction and supervision can sometimes lead to reduced motivation to learn. Therefore, it can be concluded that technological advancement cannot replace the role of English teachers in providing detailed explanations, motivation, and emotional support to learners